2011
DOI: 10.1242/dev.057943
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 proteins and autophagy regulate mitochondrial dynamics during programmed cell death in theDrosophilaovary

Abstract: SUMMARYThe Bcl-2 family has been shown to regulate mitochondrial dynamics during cell death in mammals and C. elegans, but evidence for this in Drosophila has been elusive. Here, we investigate the regulation of mitochondrial dynamics during germline cell death in the Drosophila melanogaster ovary. We find that mitochondria undergo a series of events during the progression of cell death, with remodeling, cluster formation and uptake of clusters by somatic follicle cells. These mitochondrial dynamics are depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 48 publications
2
55
1
3
Order By: Relevance
“…Recently, we have determined that mitochondrial events and the Bcl-2 family partially control PCD in mid oogenesis. 10 However, how nutritional cues link to Dcp-1, DIAP1, or mitochondria has not been determined. One candidate for the regulation of starvation-induced PCD in the ovary is the insulin signaling pathway.…”
mentioning
confidence: 99%
“…Recently, we have determined that mitochondrial events and the Bcl-2 family partially control PCD in mid oogenesis. 10 However, how nutritional cues link to Dcp-1, DIAP1, or mitochondria has not been determined. One candidate for the regulation of starvation-induced PCD in the ovary is the insulin signaling pathway.…”
mentioning
confidence: 99%
“…En effet, l'expression de debcl, supposé pro-apoptotique, protège en fait les neurones de la toxicité des protéines à polyglutamines, et, inversement, celle de buffy, qui serait anti-apoptotique, favorise cette dégénérescence neuronale [18]. Debcl et Buffy ne sont pas essentiels à la plupart des morts cellulaires développementales [19], leur rôle est restreint à certains tissus et à certains stades de développement [20]. En revanche, ils jouent un rôle important dans la mort cellulaire induite par un stress.…”
Section: Mort Cellulaireunclassified
“…En revanche, l'expression de buffy supprime les changements mitochondriaux associés à l'apoptose induite par la perte de fonction de pink1 [32], un gène codant une kinase mitochondriale dont la perte de fonction, chez l'homme, est associée à la maladie de Parkinson. Buffy et Debcl sont, par ailleurs, requis pour la mort des cellules nourricières au cours de l'ovogenèse où la perte de fonction de debcl ou de buffy conduit à une élongation du réseau mitochondrial [20]. Chez la drosophile, un lien existe entre les membres de la famille Bcl-2, la dynamique mitochondriale et la mort cellulaire.…”
Section: Mort Cellulaireunclassified
See 1 more Smart Citation
“…Homologues of Bcl-2 family member in Drosophila melanogaster are limited to the anti-apoptotic Buffy and the pro-apoptotic Debcl (Quinn et al, 2003). In previous studies, overexpression of Buffy has been shown to confer survival advantages in response to external stimuli and under conditions of stress (Sevrioukov et al, 2007;Tanner et al, 2011;Monserrate et al, 2012;M'Angale and Staveley, 2016d). A role for this gene in the mitochondrial pathway has been described during Drosophila oogenesis (Tanner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%